Conversations in human evolution. - Timbrell, Lucy, (Access archaeology., 2020)
This volume explores the breadth and interdisciplinarity of human evolution studies, presenting 20 interviews with scholars covering the broad scientific themes of quaternary and archaeological science, Palaeolithic archaeology, biological anthropology and palaeoanthropology, primatology and evolutionary anthropology and evolutionary genetics.